Pengaruh Segmentasi Pasar, Strategi Promosi & Suku Bunga Terhadap Penyaluran Kredit Serbaguna Mandiri (KSM) Di Bank Mandiri (PERSERO) TBK. Jakarta Utara - Resti Permata Arifin; Aswin Naldi Sahim; Widya Nengsih (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The banking industry faces tight competition in credit distribution, so an effective marketing strategy is needed to increase the attractiveness of credit products for customers. This study aims to analyze the effect of market segmentation, promotion strategy, and interest rates on the distribution of Mandiri Multipurpose Credit (KSM) at Bank Mandiri (Persero) Tbk - North Jakarta. The research method used is a quantitative approach. Data were collected through questionnaires on 286 samples with a Likert scale and analyzed using statistical software Structural Equation Modeling (SEM). The research sample consisted of customers who had applied for and received KSM at Bank Mandiri North Jakarta. The independent variables in this study include market segmentation, promotion strategy, and interest rates as mediator variables, while the dependent variable is KSM distribution. The results showed that market segmentation did not have a significant effect on KSM distribution, which indicated that customer mapping based on certain characteristics did not always increase the effectiveness of credit distribution. Promotional strategies contribute significantly to attracting customers to apply for KSM. Interest rates also do not have a significant effect on KSM distribution, so this factor is not the main determinant in customer decisions to apply for KSM. Meanwhile, interest rates are not a mediator variable for the relationship between market segmentation and promotional strategies on KSM distribution. In conclusion, effective marketing strategies, especially in Market Segmentation that affect Interest Rates, can increase KSM distribution. However, interest rate factors need to be considered in designing credit policies to remain competitive in the market. The recommendation of this study is for Bank Mandiri to continue to develop more specific segmentation-based marketing strategies and offer attractive promotional programs to increase KSM distribution.